2019
DOI: 10.3390/safety5020021
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Chemical Safety in Laboratories

Abstract: This study investigates the state of the perceptions of chemical safety in laboratories among undergraduate students of the Biomedical Engineering and Pharmaceutical and Chemical Engineering departments at the German Jordanian University in Jordan. A cross-sectional survey was conducted anonymously with a random sample size of 174 students. A questionnaire of 32 questions was designed with five sections: demographic data, familiarity of chemical hazard signs, attitude towards chemical laboratory safety, safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 9 publications
9
48
1
1
Order By: Relevance
“…These results support the study of Al-Zyoud, et al, in which students demonstrated fair to good in the familiarity and understanding of chemical hazard warning signs, and have poor to fair attitudes towards chemical laboratory safety (11). These attitudes may be attributed to the transition from high school to tertiary education since Chemistry is often offered during their first year of college in most colleges and universities.…”
Section: As Depicted Fromsupporting
confidence: 87%
“…These results support the study of Al-Zyoud, et al, in which students demonstrated fair to good in the familiarity and understanding of chemical hazard warning signs, and have poor to fair attitudes towards chemical laboratory safety (11). These attitudes may be attributed to the transition from high school to tertiary education since Chemistry is often offered during their first year of college in most colleges and universities.…”
Section: As Depicted Fromsupporting
confidence: 87%
“…A standardized structured self-administered questionnaire was adapted and modified from approved and published studies 11,13 (Supplementary Data S1 the questionnaire). The survey contained 43 questions, including closed-and open-ended questions, distributed across five categories.…”
Section: Survey Questionnairementioning
confidence: 99%
“…5 A variety of studies have been conducted worldwide, including the Middle East, to assess safety practices in chemistry, biology, and medical laboratories, in academic institutions and other health workplaces. [6][7][8][9][10][11] These studies indicate a lack of knowledge, and a misunderstanding of safety concepts, placing emphasis on increasing safety awareness through lectures, training, and other activities. Some studies recommend further in-depth research, with larger sample sizes, to collect more data to resolve this critical issue, 12 or to introduce safety education as an integral part of academic curricula.…”
Section: Introductionmentioning
confidence: 99%
“…These incidents can be rapid and severe or have a slow onset when there is a 'silent' release of a chemical. Also, they can also range from slight releases to full-scale main crises (1) . The term "chemical incident" might refer to anthropogenic or technological events, including:…”
Section: Introductionmentioning
confidence: 99%